Design of a control system for a mini-automatic transplanting machine of plug seedling - Yang, Qizhi; Huang, Guanlong; Shi, Xinyi; He, Mingsheng; Ahmad, Ibrar; Zhao, Xiaoqi; Addy, M. (Computers and electronics in agriculture, 2020)
•The size of the machine is 1.5*1.2*1.1 m. It is smaller than the common transplanter. It is suitable for transplanting in narrow space greenhouse.•The mechanism of variable-pitch seedling extracting was adopted to realize the technology of small distance row seedling picking and large distance static seedling throwing.•The direct and reciprocating cup type seedling separation mechanism was adopted to realize the static seedling catching and separating. In China, vegetable production system has been dominated by small and medium-sized agricultural facilities over the open-field cultivational practices. Low ceiling height and narrow width are dimensional attributes associated with most of these facilities. Due to these dimensional parametric constraints, the application of available field transplanting machinery in such facilities is a problematic subject which leads the vegetable growers towards manual transplanting. In order to meet the needs of small and medium-sized agricultural facilities for automatic vegetable transplanting, a smaller size wireless remote-controlled automatic transplanting machine was designed, which can transplant seedlings quickly in the greenhouse and by considering the stainability of environment electric power was adopted to drive all the mechanisms. In the process of agricultural production, the control system of agricultural machinery plays an important role in the degree of automation of mechanical equipment. Therefore, this paper focuses on the design of the control system of the newly premeditated automatic transplanting machine. The hardware of the control system is separated into three portions: the sensors for signal acquisition, the programmable controller for signal processing, and the driving elements for specific actions. PLC (Programmable logic controller) is adopted as the central control system of the transplanting machines which controls the automatic movement of seedlings tray carrier, seedlings extraction and feeding, and seedlings transmission to the planting units automatically. In order to control the overall movement of seedling transplanting machine, a microcontroller is adapted to control the hub and steering motor. The key driving elements of the control system are solenoid valves and electric motors which controls the action of pneumatic air cylinders and linear movement of different parts of machine respectively. The overall software design of the control system is accomplished, together with coordinated motion between components, control flow design and control program writing. In order to test the motion coordination of each component and the rationality of the control system of the Mini-Automatic transplanting machine, different planting frequencies were set to record the success rate of seedling collection and transplanting. The results of the trials exhibited that at the planting frequencies of 40, 50 and 60 plants/row/min the overall success rates were noted 98.6%, 97.2% and 96.5% respectively. It shows that the key parts of the transplanting machine are synchronized in motion, accurate in positioning, reasonable in assembling the control system and stable in operation, which meets the requirements of transplanting seedlings in the dry land.